Examining Why the Canadian Federal Government Placed an Orphan Drug Strategy on Their Decision Agenda Now - Mark Gary Embrett (McMaster University Library Press, 2014)
The Ministry of Health's announcement of a National Orphan Drug Framework on 3 October 2012 was the first federal public acknowledgement of orphan drugs since the 1997 Drugs Directorate (DD) policy statement. The reform primarily announced an Orphan Drug Policy for Canada. This paper explains why the government decided to make this announcement now. Media and Parliamentary documents were analyzed for their use of symbols, numbers, and language in causal stories told by political actors. The initial story was that Canada's population was too small and the cost too high for an orphan drug policy. Over the next fifteen years, a powerful interest group, the Canadian Organization for Rare Disorders (CORD), mobilized the rare disease community into a cooperative effort that generated collective action. They redefined the DD story from one of natural causes, to inadvertence, and finally to intentional causation. Their story invoked a federal response because it blamed the government directly for not acting on behalf of the 3 million Canadians with rare diseases, when patients in other countries were receiving better care.